G527(P) Buckle fractures of the distal radius: increased efficiency and cost savings through a new management pathway. (27th April 2015) - Knight, KM; Hadley, G; Parikh, A
Abstract : Context: This quality improvement project took place in a tertiary centre, involving the Paediatric A&E and Orthopaedic teams. It required minor changes in practice by paediatric A&E doctors and nurses, and affected children between 3 and 15 years who presented with a radial buckle fracture. Problem: Fractures are a common reason for children to attend A&E. During the summer months, fracture incidence tends to increase. Our summer fracture clinics were quickly filling up with minor injuries (up to a 3 week wait) and this impacted upon patients with severe injuries who needed urgent orthopaedic review. Buckle fracture of the distal radius was one type of injury seen with disproportionate frequency. Assessment of problem and analysis of its causes: A joint paediatric/orthopaedic meeting addressed the issue of overbooked clinics. The orthopaedic team noted that many patients with a buckle fracture were discharged with no intervention at their first fracture clinic appointment. Analysing the previous summer's buckle fractures, over 90% were managed with a cast, repeat x-ray and fracture clinic review. Our practice was outdated – recent studies advocate conservative management of this injury with a removable splint, and no further review. Intervention: A new management pathway for buckle fractures was created. If a set of criteria were met, the patient could be discharged with a splint rather than a cast. The criteria were: fracture of radius only; no break in opposite cortex; minimal angulation on AP and lateral X-rays; no child protection concerns. The emergency department sourced paediatric splints. Parents were educated before leaving, and given an information leaflet. As a 'safety net', all X-ray reports were reviewed by a registrar – if the fracture was more serious than first thought, the child was recalled. Study design: All children with suitable fractures during June–July 2014 were managed according to the new guideline. Their records were later analysed and a follow up telephone survey evaluated how the child and family had coped with the splint. Clinic waiting times were monitored. Strategy for change: A draft guideline for buckle fracture management was agreed between paediatric A&E and orthopaedic doctors, and disseminated by email to all A&E staff. Posters displayed around the department reminded everyone of the change in practice. A parent information leaflet was produced in the two common languages of our area. During an initial two week trial period, staff were encouraged to share their experiences of using the new guideline, which allowed certain details to be amended before the two month study period. Measurement of improvement: Fracture clinic bookings were monitored, and a telephone survey evaluated parental satisfaction with management. We used electronic records to check whether there were any post fracture problems presenting to A&E, and also calculated how much money and time the department would save using this new pathway. Effects of changes: In two months: 37 fewer fracture clinic appointments were booked, equating to three full clinics' worth of appointments. 22.2 nursing hours were saved as fewer casts were applied. Only two out of 24 fracture clinics that took place were overbooked. There was a 65% response rate in the telephone survey; all families contacted were very happy with the removable splint. Of those who did not respond, none reattended. The department saved over £90 per child. The new guideline is now our standard practice. Lessons learnt: Modernising guidelines in line with latest research may lead to greater efficiency, and significant savings. Message for others: Cooperation between different teams can be the catalyst for effective change.